Eksistensi Radio Melalui Konvergensi Siaran di Era Digital - Damayanti, Ratih; Santoso, Teguh Setiawan Imam; Tecoalu, Melitina (Jurnal Pustaka Komunikasi, 2024)
Radio is a communication medium that must now be able to compete with new media which is currently increasingly massive. The aim of this research is to find out how national private broadcast radio in West Java is able to maintain its existence and the strategies it implements to continue to exist amidst competition with digital information platforms that currently exist. Research respondents were managers of local radio stations in West Java, especially those in Bandung, Cimahi, Sukabumi and Cirebon. This research uses qualitative methods by describing the result of questioners and interviewing and then processing them in the form of descriptive narratives and pie diagram. The results of this research are that almost all private broadcast radio stations in the West Java region that were respondents implemented a convergence strategy to maintain their existence and made changes to their broadcast model management. Some of the convergence strategies implemented are broadcasting via digital streaming, creating more interesting broadcast program content with an audio-visual style such as podcasts, choosing broadcasters who have popularity and character, upgrading broadcast equipment, having social media as a branding and content publication medium, and upload content to YouTube media. This convergence strategy is also carried out to increase interest and the number of advertisers so that they can continue to choose radio as a medium for marketing the products and services offered more widely and in a contemporary style.